Inherited variation in the xenobiotic transporter pathway and survival of multiple myeloma patients. (6th August 2018) - Macauda, Angelica; Castelli, Eleonora; Buda, Gabriele; Pelosini, Matteo; Butrym, Aleksandra; Watek, Marzena; Kruszewski, Marcin; Vangsted, Annette Juul; Rymko, Marcin; Jamroziak, Krzysztof; Abildgaard, Niels; Haastrup, Eva Kannik; et al.
Summary: Over the past four decades, remarkable progress has been made in the treatment and prognosis of multiple myeloma (MM), although it remains an incurable disease. Chemotherapy resistance is a major hurdle for treatment efficacy. Drug resistance can be innate and so driven by genes involved in the drug metabolism pathways. We performed an association study of 71 germline variants within the major genes in those pathways ( ABCB1, ABCC2, ABCG2, and their regulators NR1I2/PXR and NR1I3/CAR ) in theI nternationalM ultipleM yeloma rESE arch (IMMEnSE) consortium, consisting of 1365 MM cases with survival information recruited in 5 European countries. Two of the SNPs showed a significant association with the survival of MM patients, namely rs2235013, located in ABCB1 [Hazard ratio (HR) = 1·52, 95% confidence interval (CI) = 1·18–1·95, P  = 0·00087], and rs4148388, located in ABCC2 (HR = 2·15, 95% CI = 1·44–3·22, P  = 0·0001). ABCC2 plays an essential role in transporting various anticancer drugs, including several used against MM, out of the cell. In silico analyses predict that the variant alleles of four SNPs in linkage disequilibrium with ABCC2 ‐rs4148388 are associated with increased gene expression. Overexpression of ABCC2 increases drug clearance and therefore may induce drug resistance mechanisms. In conclusion, we found a promising association between ABCC2‐ rs4148388 and MM outcome that is supported by a plausible biological explanation.